Q1: 20 points Q2: 40 points Q3: 25 points Q4: 15 points Total: 100 points
Question text is in black, solutions in blue.
FALSE. The 1 and 6x are correct but it should be 6x2.
FALSE. The x3 term should be deleted.
TRUE. We choose which element of B is hit twice, then which two elements of A hit it, then how the other three elements of A go 1-1 to the other three elements of B.
FALSE. If we change the first condition to "at most three parts" it is correct. We could also change the second condition to "with largest part of size exactly three".
FALSE. The value x2 could be anything. Since this is a third-order recurrence, we would need three initial conditions to determine it uniquely, but we are given only two.
TRUE. We can find g(x) in principle by long division, since the constant term of the dividend is 1.
FALSE. That is the number of ways to distribute r distict treats to r distinct dogs.
FALSE. The sum should be from 0 to n.
FALSE. The last "-1" term should be "-1×0n", i.e., 0.
FALSE. Both have 11!/2! anagrams, since the 11! permutations of each count each word twice. Exchanging the two S's in BASINGSTOKE or the two E's in BELCHERTOWN leads to the same anagram.
It is perhaps easiest to begin by giving three treats each to Cardie and Duncan, then considering the ways to distribute the other seven treats. Scout could get 0, 2, 4, or 6 of these. If she gets 0, there are C(7+2-1, 2-1) = 8 ways to divide the other 7 treats among the other two dogs. If Scout gets 2, there are C(6+2-1, 2-1) = 6 ways to divide the others. Similarly there are 4 ways if Scout gets 4 and 2 ways if Scout gets 6, for 8+6+4+2 = 20 ways in all.
For Cardie and Duncan, the GF for the ways to give them three or more treats is
x3 + x4 + x5 + ... = x3/(1-x).
For Scout, the GF for the number of ways to give her an even number of treats
is 1 + x2 + x4 + ... = 1/(1-x2). (Someone
wrote this as (1/2)[1/(1-x) + 1/(1+x)], which is also correct.)
Writing (1-x2) as (1-x)(1+x), the total GF evaluates to
x6 × 1/(1-x)3 × 1/(1+x). To get the
x13 coefficient of this, we need the x7 coefficient
of f(x)g(x), where f(x) = 1/(1-x)3 = ∑C(r+1, 2)xr,
and g(x) = 1/(1+x) = ∑(-1)rxr. So we have the sum
for i from 0 to 7 of C(i+1, 2)(-1)7-i, or -1 + 3 - 6 + 10 - 15 + 21
- 28 + 36 = 2 + 4 + 6 + 8 = 20.
The EGF for Cardie and Duncan is each x3/3! + x4/4! + x5/5! + ... = ex - 1 - x - x2/2. The EGF for Scout is 1 + x2/2! + x4/4! + ... = (ex + e-x)/2. We multiply these three expressions together (getting a sum of 32 terms), evaluate the x13 coefficients of each, and add the answers. This coefficent, multiplied by 13!, is the number of ways to give 13 distinct treats to the three dogs, following the conditions.
The total number N is C(13+3-1, 3-1) = C(15, 2) = 105 by a stars and bars
argument. To determine the size of A1 and A2, we break
into three cases by whether the dog in question violates the condition by
getting 0, 1, or 2 treats. In each case the remaining treats must be
distributed between the other two dogs, in 14, 13, or 12 ways respectively, so
these two sets each have size 14+13+12 = 39. To get the size of A3,
we divide into cases for Scout getting 1, 3, 5, 7, 9, 11, or 13 treats. In
each case the others are distributed between Cardie and Duncan, in
respectively 13, 11, 9, 7, 5, 3, and 1 ways, for 49 ways in total.
So the correct number of ways to follow the rules is
105 - 39 - 39 - 49 + |A1 ∩ A2|
+ |A1 ∩ A3/sub>|
+ |A2 ∩ A3|
- |A1 ∩ A2 ∩ A3|.
You were not required to go further than this, but the first two
two-way intersections each have size 19, the third two-way intersection
has size 9, and the three-way intersection has size 5. This makes the
sum 105 - 39 - 39 - 49 + 19 + 19 + 9 - 5 = 20.
a2 = -7, a3 = 7, a4 = 21, a5 = 107. b2 = b4 = 1, b3 = b5 = -1.
The characteristic polynomial is α2 - 2α - 3 = 0, which has roots 3 and -1. So the general solution is A3n + B(-1)n. Substituting b0 gives A + B = 1, and b1 gives 3A - B = -1. Adding these two equations gives 4A = 0, so A = 0, B = 1, and the specific solution is bn = (-1)n.
We know that the specific solution will be of the form an = B1n + B0. We have that B1n + B0 = 2(B1(n-1) + B0) + 3(B1(n-2) + B0) + 16n - 36. Equating the terms in n gives B1 = 5B1 + 16, which solves to B1 = -4. Equating the constant terms gives B0 = -8B1 + 5B0 - 36 which gives -4B0 = -4 or B0 = 1. So the specific solution is an = -4n + 1.
Combining the answers above, the general solution is an = A3n + B(-1)n - 4n + 1. Substituting a0 gives -3 = A + B - 0 + 1, or A + B = -4. Substituting a1 gives 3 = 3A - B - 4 + 1, or 3A - B = 6. Adding the equations gives 4A = 2 or A = 1/2, and thus B = -9/2.
We first pull the C(n, i) term out of the inner sum since it is invariant
under j. We now have, for each i, the binomial expansion of (1-2)i.
The sum for all i of C(n, i)(-1)i is just the binomial expansion of
(1-1)n, which is 1 for n = 0 and 0 for all positive integer n.
It's natural to try to prove this result by induction. The base
case of n=1 works fine: We have three terms in the sum, for
(i, j) = (0, 0), (1, 0), and (1, 1), and these are
(-2)0C(1, 0)C(0, 0), (-2)1C(1, 1)C(1,
0), and (-2)0C(1, 1)C(1, 1), giving 1-2+1 = 0.
So we assume that the given sum is 0, and look at the sum
for i from 0 to n+1 of the sum for j from 0 to i of
(-2)i-jC(n, i)C(i, j). Most of you who attempted
this proof made a key mistake at this point. None of
the terms of the sum in the IH occur in the sum in the
inductive goal. The former all have a term of C(n, i), while
the
latter have C(n+1, i). We indeed add n+2 new terms, for the
case of i = n+1. This gives us the sum for j from 0 to n+1 of
(-2)n+1-jC(n+1, n+1)C(n+1, i), which we might
recognize
as the binomial expansion of (1-2)n+1 =
(-1)n+1.
But we also get, for each (i, j) with 0 ≤ i ≤ n and 0
≤ j ≤ i, a term for the difference between the (i, j)
terms in the two sums. By Pascal's Identity, C(n+1, i) - C(n,
i) is equal to C(n, i-1), so we have the sum for all such i
and j of (-2)i-jC(n, i-1)C(i, j). The only way I
can
see to evaluate this is to follow the method I used above to
solve the original problem! We pull the C(n, i-1) out of the
inner sum, making it the sum for j from 0 to i of
(-2)i-jC(i, j), and this is (1-2)i.
Thus the outer sum becomes the sum for i from 0 to n of
C(n, i-1)(-1)i. We can rewrite this by letting k =
i-i to get the sum for k from 0 to n-1 of C(n,
k)(-1)k+1. (We ignore the zero term for k = -1.)
If this sum were from 0 to n, we would have (-1) times the
binomial expansion of (1-1)n, which is zero. So
our sum is actually -1 times the missing k = n term, and that
missing term is C(n, n)(-1)n+1.
So the sum for the changed terms exactly cancels the sum
for the new terms, and the sum in the inductive goal has the
same value as the sum in the IH, which we assume to be 0.
Again, I didn't expect you to carry out this inductive
proof, and no one did so, but I went through it to show that
if you didn't make the mistake I pointed out, it was at least
theoretically possible.
Last modified 2 December 2016